2015
DOI: 10.1039/c5cc07588b
|View full text |Cite
|
Sign up to set email alerts
|

N-Heterocyclic carbene ligands bearing poly(ethylene glycol) chains: effect of the chain length on palladium-catalyzed coupling reactions employing aryl chlorides

Abstract: N-Heterocyclic carbenes bearing poly(ethylene glycol) chains of different lengths have been designed and employed as ligands in palladium-catalyzed coupling reactions. The catalyst system having longer chains was found to be highly efficient for Suzuki-Miyaura coupling and borylation reactions employing aryl chlorides under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Owing to their significant advantages, including widely commercial availability, biocompatibility, chemical and thermal stability and ease to be derived, PEGs have been widely used as phase-transfer catalysts (PTC) or in the preparation of water soluble ligands for aqueous organic reactions during the past decades [6869]. More recently, several PEG-functionalized azolium salts have been synthesized as water soluble NHC precursors for aqueous Pd-catalyzed cross-coupling reactions [5659 70]. Fujihara also pointed out that the flexible linear long-chain structure of PEGs could wrap and stabilize the metal center and thus significantly enhanced the catalytic efficiency [70].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to their significant advantages, including widely commercial availability, biocompatibility, chemical and thermal stability and ease to be derived, PEGs have been widely used as phase-transfer catalysts (PTC) or in the preparation of water soluble ligands for aqueous organic reactions during the past decades [6869]. More recently, several PEG-functionalized azolium salts have been synthesized as water soluble NHC precursors for aqueous Pd-catalyzed cross-coupling reactions [5659 70]. Fujihara also pointed out that the flexible linear long-chain structure of PEGs could wrap and stabilize the metal center and thus significantly enhanced the catalytic efficiency [70].…”
Section: Resultsmentioning
confidence: 99%
“…More recently, several PEG-functionalized azolium salts have been synthesized as water soluble NHC precursors for aqueous Pd-catalyzed cross-coupling reactions [5659 70]. Fujihara also pointed out that the flexible linear long-chain structure of PEGs could wrap and stabilize the metal center and thus significantly enhanced the catalytic efficiency [70]. Therefore, we chose PEG as functionalization group to prepare water soluble catalysts.…”
Section: Resultsmentioning
confidence: 99%
“…Shi et al synthesized a series of short‐chain alkyl and/or PEG chain ferrocenylphospine–imidazolium salts, and they found that the catalysts bearing PEG chains showed higher catalytic activity for Pd‐catalyzed Suzuki reaction in aqueous solvents . Very recently, NHCs bearing different lengths of PEG chains were synthesized by Fujihara et al and used to promote Pd‐catalyzed Suzuki reactions, the catalysts with longer PEG chains showing better performance . We found PEG‐functionalized NHC ligands were efficient for recyclable Pd‐catalyzed Suzuki reactions in water, and recently we utilized short alkyl chain‐ and glucopyranoside‐based NHC precursors for Pd‐catalyzed Suzuki reactions, which smoothly promoted the Suzuki coupling in ethanol (95%) with a typical catalyst loading of 0.1 mol% .…”
Section: Introductionmentioning
confidence: 80%
“…Taking the hydrophilicity and flexibility of bulky poly (ethylene glycol) (PEG) chains into consideration, the incorporation of PEG chains into NHC ligands could effectively improve simultaneously the water solubility and steric hindrance of the host materials. However, up to the present, there have been only a few reports of NHC ligands containing PEG groups . The first example was reported by Hong and Grubbs who used a PEG‐decorated NHC–Ru compound for aqueous olefin metathesis .…”
Section: Introductionmentioning
confidence: 99%
“…Fujihara et al [177] reported NHCs bearing poly(ethylene glycol) chains of different lengths like L117 (Fig. 14) and used as ligands in Pd-catalyzed coupling reactions.…”
Section: April 2019mentioning
confidence: 99%